Complete Heart Block Secondary to Microscopic Polyangiitis: A Rare Case Presentation - Filice, Giuseppe (Cureus, 2020)
The potential etiologies of third-degree complete heart block include idiopathic, pathologic, and iatrogenic causes. We present a rare case of complete heart block in an elderly woman with microscopic polyangiitis (MPA), who presented with dyspnea on exertion and dizziness.